Normative baseline SCAT5 scores in a population of United States olympic athletes - Pierpoint, L.; Zdziarski, L.; Taylor, D.; Moreau, W.; Nabhan, D. (British Journal of Sports Medicine, 2021)
Background The Sport Concussion Assessment Tool 5th Edition (SCAT5) is the most recent version of the concussion evaluation tool used by clinicians to evaluate athletes with suspected concussions.